Screening and Optimising Metal Salt Concentration for Harvesting Nannochloropsis Sp. by Flocculation - Chua, Gek Kee; Nur Anis, Saarani (Malaysian Technical Universities Network (MTUN), 2015)
Biodiesel, a renewable fuels that are non-toxic and biodegradable, is constantly increasing in demand as the reservoir of fossil fuel are depleting. The microalgae biomass with high oil content is significant as a sustainable resource for biodiesel production. Production of biodiesel using microalgae biomass appears to be a feasible alternative due to no confliction with food supply compared with the first generation biofuels. This report deals with the screening and optimisation of metal salts for harvesting marine microalgae by flocculation. The metal salts studies are ferric chloride, aluminium sulphate and ferric sulphate. Wild Nannochloropsis strains of microalgae were cultivated aseptically in sea water for 7 days, after that the microalgae was harvested by using flocculation step with different concentration of metal salt. In order to monitor the efficiency of the metal salt, the turbidity region of microalgae in glass cylinder before and after flocculation was observed. Besides that cell dry weight was also compared for three flocculation agent used. The most efficient metal salt was then further optimized for its best performed concentration and pH. Chloride salts (FeCl3) was found to be more efficient in comparison with sulfate salts (Al2(SO4)3 and Fe2(SO4)3) in harvesting microalgae. Ferric Chloride was further optimized, where the optimum pH and concentration of FeCl3 are 8.5 and 1.0 M, with flocculation efficiency of 90 % and cell dry weight of 3.8 g. In conclusion, 1.0 M ferric chloride salt at pH 8.5 is optimum in harvesting Nannochloropsis microalgae by flocculation.